2013
DOI: 10.1093/aje/kws380
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Effectiveness of Isolation and Decolonization Measures in Reducing Transmission of Methicillin-resistant Staphylococcus aureus in Hospital General Wards

Abstract: Infection control for hospital pathogens such as methicillin-resistant Staphylococcus aureus (MRSA) often takes the form of a package of interventions, including the use of patient isolation and decolonization treatment. Such interventions, though widely used, have generated controversy because of their significant resource implications and the lack of robust evidence with regard to their effectiveness at reducing transmission. The aim of this study was to estimate the effectiveness of isolation and decoloniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 29 publications
0
42
0
1
Order By: Relevance
“…Our results are also consistent with prior mathematical modeling studies in adult patient populations. Worby et al 26 reported that the combination of isolation and decolonization reduced transmission by 64%, with the majority of observed transmission attributed to unisolated and untreated MRSA carriers. Gurieva et al 27 used a stochastic simulation model to assess the impact of decolonization and found that decolonization was highly effective even with imperfect efficacy in eliminating carriage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are also consistent with prior mathematical modeling studies in adult patient populations. Worby et al 26 reported that the combination of isolation and decolonization reduced transmission by 64%, with the majority of observed transmission attributed to unisolated and untreated MRSA carriers. Gurieva et al 27 used a stochastic simulation model to assess the impact of decolonization and found that decolonization was highly effective even with imperfect efficacy in eliminating carriage.…”
Section: Discussionmentioning
confidence: 99%
“…This is further evidenced by the visible decline, but not elimination of MRSA acquisition in the NICU during the study period (Figure 3). This background risk of acquisition, not linked to patient-to-patient transmission, has been well-described using mathematical modeling approaches, 26 and has been shown to account for the majority of MRSA acquisition in adult settings. 28 Similarly, Price et al report that only 18.9% of S. aureus acquisitions in an adult intensive care unit could be explained by patient-to-patient transmission when whole-genome sequencing was used.…”
Section: Discussionmentioning
confidence: 99%
“…The identification, isolation, and decontamination of patient carriers are associated with reduced MRSA transmission, although the evidence for this is limited and debated 3, 4, 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…193 We used uninformative exponential priors Exp(0.001) for the transmission parameters 194 α, β, and µ. Parameters for the proposal distribution were tuned in order to ensure 195 rapid convergence. Similar to [26], we estimated the sensitivity φ and importation 196 parameter f using uninformative beta prior distributions Beta (1,1). The initial 197 bacterial load E 0 was approximated by ν µĪ withĪ being the mean prevalence in the 198 ward.…”
mentioning
confidence: 99%
“…The results of our analysis build on a data-augmented MCMC algorithm [19,26]. 464 Markov chain Monte Carlo sampling is a powerful tool to estimate posterior parameter 465 distribution whenever the likelihood is analytically intractable.…”
mentioning
confidence: 99%